HarpyGame: A Customizable Serious Game for Upper Limb Rehabilitation after Stroke - Cyrino, Gabriel; Tannús, Júlia; Lamounier, Edgard; Cardoso, Alexandre; Soares, Alcimar (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR), 2020)
Stroke is the most common disease that leads to the dexterity impairment of the upper limbs. Serious games have emerged as an advantageous and enjoyable alternative to rehabilitation treatment when compared to traditional therapies. This work presents the development of a customizable serious game, based on Virtual Reality techniques to achieve a more natural and intuitive interface. The game was developed to allow different types of input devices. In so doing, the system consists of a control panel for patient management and customization of the game, a serious game with a realistic environment with levels and adaptive tasks, and a database. The research considered the assistance of physiotherapists to provide protocols that the game followed. Results indicated significant acceptance by the patients, implying the system’s potential use in the post-stroke rehabilitation process of the upper limbs.